Early experience with lateral lumbar total disc replacement: Utility, complications and revision strategies. (May 2017) - Malham, Gregory M.; Parker, Rhiannon M.
Highlights: XL-TDR is a minimally invasive alternative for motion preservation. Revision surgery for XL-TDR dislocation is more straightforward than anterior TDR. Correct prosthesis sizing and contralateral annulectomy mitigates dislocation risk. Abstract: Lumbar total disc replacement (TDR) is an alternative to interbody fusion for the treatment of symptomatic degenerative disc disease. Traditionally, lumbar TDR is performed via an anterior retroperitoneal approach with regional risks of vascular and visceral injury. The direct lateral retroperitoneal, transpsoas approach avoids mobilisation of the great vessels and preserves the anterior longitudinal ligament, thereby maintaining physiological limits on motion. This study aimed to (i) report one site's early experience with lateral lumbar TDR and (ii) provide case examples illustrating the utility, complications and revision strategies of the XL-TDR device. Data were collected prospectively on the first 12 consecutive patients treated with XL-TDR. Patient outcomes included pain (VAS), disability (ODI), and quality of life (SF-36 PCS and MCS). Mean follow-up was 27.5 months (range 18–48 months). Patients had significant improvements in back (74%) and leg (50%) pain, ODI (69%), PCS (50%) and MCS (39%) ( P  < 0.05). Two patients had early prosthesis dislocation due to prosthesis undersizing. The same skin incision was used to retrieve the XL-TDR and perform salvage lateral lumber interbody fusion, with solid fusion by 12 months. Lumbar TDR using the XL-TDR via a lateral transpsoas muscle-splitting approach is a minimally invasive alternative to anterior retroperitoneal exposures for motion preservation. Correct sizing of the XL-TDR and complete contralateral annulectomy with annulus box cutters mitigates the risk of lateral dislocation. Revision surgery for lateral dislocation of the XL-TDR is more straightforward compared to anterior TDR dislocation.